A Proposal Development of Model Design Interactive E-Book Using Generative AI - Nuansri, Wisarut; Kultawanich, Kulachai (Rajapark Journal, 2024)
The objective of this research is to 1) study guidelines and develop a proposal model for designing an interactive e-book to get to know BCG with generative AI. 2) to collect specialist opinions through interviews. 3) to evaluate the design proposal model of an interactive e-book with generative AI. The researcher selected a sample group of 12 specialists using purposive sampling. This group was divided into two subgroups, as follows: Group One consists of specialists who are conducting interviews with 6 specialists to obtain their comments on the generated proposal model, and 6 specialists in Group Two are responsible for evaluating the proposal model. The research instruments included an e-book design proposal model using generative AI and an interactive e-book for getting to know BCG that used a proposal model in development. The instruments of data collection methods encompass specialist interviews from the fields of technology, education technology, and agricultural development, as well as certification evaluation forms for the proposal model. The researcher performed a content analysis of the interview and discovered that the specialists’ comments were consistent, indicating that the proposed model was suitable. The innovative concepts and ideas were in line with the latest advancements in technology. The human role as an accuracy verifier had significant advantages, particularly in the context of agricultural media and other forms of media. This role also contributed to the creation of a growing body of new research. A proposal model evaluation determined that the interactive e-book proposal model had an excellent overall rating (Avg. 4.57 Std. 0.30). Data from evaluation forms using fundamental statistical measures like the average and standard deviation.